Effectiveness of Public Service Policy Based on Mobile Passport Application at Immigration Offices Class 1 Surabaya Immigration Checkpoints - Basari, Aldi Ferdian; Mustofa, Amirul; Widyawati, Widyawati (PT. Anagata Sembagi Education, 2024)
The Mobile Passport application represents the government's initiative to modernize and streamline public services in immigration. This digital solution allows users to manage passport applications without visiting the Immigration Office. This study examines the effectiveness of the Mobile Passport application policy at the Class 1 Immigration Office, Surabaya, using five key indicators: program understanding, target accuracy, timeliness, goal achievement, and real change. A qualitative approach was employed, collecting data through interviews with users, direct observations, and analysis of user reviews on Google Play Store. Additional data were obtained from policy-related documents and reports. Findings indicate that 75% of users benefited from the application, particularly in registration and tracking passport status, though 25% still struggle with technical aspects. Furthermore, 85% of users agreed that the application simplifies passport administration. Despite this, issues like system stability and login difficulties persist. The study concludes that the Mobile Passport application positively impacts public service efficiency. However, further improvements in digital literacy and technological infrastructure are needed to enhance user experience and optimize policy outcomes. This research highlights the importance of addressing technical challenges and user education to achieve comprehensive success in digital public service initiatives.